Minerals and heavy metals in Labisia pumila var. alata folia of Selected Geographic Origins - Ade Chandra Iwansyah; Noorazizah Zainal Abidin; Mashitah Mohammad Yusoff (Jurnal Kartika Kimia, 2019)
Labisia pumila var. alata leaves (LP) with a long history of use folk remedy and endemic to the Malay Archipelago, is now supplied worldwide as ingredient of functional foods and beverages. Minerals and heavy metal concentrations in Labisia pumila var. alata folium (LP) of selected geographic origin based on microwave-assisted sample digestion and inductively coupled plasma mass spectrometry (ICP-MS) were determined. Fifteen elements comprising minerals (Ba, Ca, Cr, Co, Cu, Fe, K, Mg, Na, Ni, Rb and Zn) and heavy metals (As, Cd and Pb) were analyzed with an inductively coupled plasma – mass spectrometer (ICP-MS). The highest nutrient concentration was measured in LP from Tilu Mountain (Cu, Na, K, Mg and Zn). The highest values of Ba, Ca, Co, Cr and Fe were detected in LP from Raub. Ni and Rb were highest in LP from Cibeundey Village. As was highest in LP from Raub (0.04 ± 0.00 mg/kg). The highest Pb contents were in LP from Tilu Mountain (2.90 ± 0.10 mg/kg) and LP from Halimunan-Salak Mountain (3.12 ± 0.03 mg/kg), all of which were well within the permissible limits as specified by the U.S. FDA for edible plant parts.